Websites and Contemporary Authors: the case of Olga Tokarczuk - Stefania Spinelli (RiCognizioni)
Assuming that writers' web pages, as a response to the demands of modern communication, can represent significant research material, this article explores Olga Tokarczuk’s digital presence through two key websites: the one hosted by her publisher and the Olga Tokarczuk Foundation’s website. The author’s Wydawnictwo Literackie website is static, serving primarily as a promotional tool for the Nobel Prize’s publications, while the Foundation’s website is more dynamic, focusing on social and cultural initiatives and containing a database as well, conceived as an archive. I shall argue that both websites serve more traditional roles in showcasing Tokarczuk’s work rather than fostering direct engagement with her audience. Despite her celebrity status, Tokarczuk’s website presence reinforce her established public identity but doesn’t seem to align with an influencer model. This suggests that Tokarczuk’s approach is more focused on cultural discourse through her writing and actions than on shaping her persona through her websites.